Effect of the connection structure of zirconia dental implants on biomechanical properties - Sun, Fei; Xu, Libing; Han, Jianmin; Xu, Hai; Li, Xinchang; Lin, Zeng (Journal of the mechanical behavior of biomedical materials, 2025)
The connection structure of zirconia dental implants significantly influences their biomechanical behavior and plays a crucial role in the overall service performance of the implant system. This study aims to compare the stress distribution of zirconia implants featuring various internal connection structures under different working conditions. Four distinct types of connection structures were designed for zirconia dental implants: triangular, quadrilateral, hexagonal, and hexalobular plus connections. Additionally, the finite element method was employed to analyze these structures under three working conditions: a static load test model, a bone level model, and a torsion model. Results indicated that in the static load test model, the hexagonal structure experienced the highest stress value at 1284.9 MPa due to its thin neck wall, whereas the hexalobular plus connected implant exhibited the lowest stress value at 1252.9 MPa. In the bone level model, the triangular connection structure demonstrated poor stress distribution for cortical bone and cancellous bone at 69.606 MPa and 7.8191 MPa, respectively. Conversely, the hexalobular plus connection yielded superior stress results for cortical bone and cancellous bone, with values of 66.24 MPa and 5.1327 MPa, respectively. In the torsion model, the hexalobular plus-connected implant exhibits the highest stress value at 237.6 MPa, while maintaining the smallest force transmission angle. Therefore, given that the abutment necessitates a greater range of installation angles and improved torque transmission, the hexalobular plus connection structure may represent the optimal choice.
Keywords: biomechanika; Zirconium; Finite Element Analysis; Mechanical Tests; zubní implantáty; Mechanical Phenomena; Biomechanical Phenomena; FEA; Zirconia; mechanické testy; Stress, Mechanical; mechanické jevy; Dental Implants; Connection structure; mechanický stres; analýza metodou konečných prvků; Dental implant; testování materiálů; Materials Testing; zirkonium